The Comparison Between Norotate and Promax Rotations of Biplot Simulation in The Management of Bali Cattle’s Breeding Farms on Integrated Farming System - I Putu Sampurna; Tjokorda Sari Nindhia; I Made Sukada (Journal of Veterinary and Animal Sciences, 2020)
This study aims to determine the comparison between Norotate Rotation and Promax Rotation (90) of Biplot Simulation in the management of Bali Cattle Breeding Farms on Integrated Farming System (Simantri). It used to determine the difference of coordinates between the variables and also obtain the information about the difference in the proximity of the coordinates between livestock groups.The study conducted on Simantri who had livestock groups in Badung Regency, Bali in which the data collected were analyzed by factor analysis with Norotate Rotation and Promax Rotation (90). The variable of this study was a livestock management which included management of cows, calves, feed, cowshed, environmental,and the objects of the study were thelivestock groups. The Biplot simulation used to determine the coordinates of the livestock groups determined based on the Factor Scores Method Regression Analysis. The results with different rotations caused differences in the magnitude of the arrow angles and directions between management of cows, calves, feeds, cowshed and environmental which also followed by differences in the coordinate systems of the livestock groups. The angle between management of cows, calves, feeds, cowshed, and environmental do not show the magnitude of the correlation between them. It can be stated that the coordinates of Livestock groups on Promax Rotation (90) are more specific than Norotate Rotation, therefore it is easier to distinguish the different scores between the variables on the Livestock groups.